Climate changes have alleviated constraints on forest carbon storage capacity since 1970 in most of the Northern Hemisphere - Fang Wu; Junwen Jia; Cheng Li; Yun Cao; Junfang Zhao; Xiaodong Yan; Xuefeng Cui (Ecological Indicators)
Global climate action is urgent, with forest carbon stock critical for mitigating climate change, yet vulnerable to its impacts. However, the long-term dynamics of climate-driven forest carbon stock have not fully been expressed. Here, we introduce the Forest Carbon Stock Accumulated by Single Tree growth (FAST) framework and constructed a counterfactual scenario to isolate and quantify the climate-driven changes in forest total carbon stock for 1901–2022. Results show that breakpoints in climate-driven forest carbon stock occurred post-1970 are observed over 62% of the study areas, with Europe experiencing the latest, followed by Asia, and North America the earliest. Furthermore, we observe a prevailing increasing trend in climate-driven forest carbon stock, especially in post-breakpoints period (from 53% to 68%), indicating that climate changes have alleviated constraints on forest carbon storage capacity in most areas. FAST can be utilized for historical, current and future forest carbon stock estimation, providing scientific support for sustainable forest management decisions.